Konstruksi Realitas Religius dan Produksi Subjek Iman: Analisis Kritis atas Dokumen Pembekalan bagi Para Pendamping Calon Penerima Komuni Pertama di Paroki St. Paulus Pringgolayan 2025 - Yustinus Joko Wahyu Yuniarto (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
This article critically examines the training program document for mentors of First Communion candidates at St. Paul Pringgolayan Parish as an institutional religious text. The study employs Peter L. Berger’s theory of the social construction of reality and Michel Foucault’s discourse analysis of power as its analytical framework. Using a qualitative interpretive method, the research conducts an in-depth textual analysis of the document’s narrative structure, normative language, actor relations, and mechanisms of legitimation. The findings reveal that the text is not merely a plan and report of pastoral activities; it also functions as an institutional apparatus that reproduces religious reality while shaping subjects of faith through pedagogical, ritual, and administrative systems. This article argues that pastoral documents can be understood as pastoral social technologies that operate through language to structure religious experience, regulate the distribution of authority, and instill norms of faith practice. These findings contribute to the sociology of religion by demonstrating how faith formation practices at the local level constitute a concrete locus of interaction between the construction of religious meaning and the operation of discursive power.